Employee Mobility and Interfirm Relationship Transfer - Raffiee, Joseph (Strategic Management Journal, 2017)
[Research summary: Employee mobility can erode competitive advantage by facilitating interfirm knowledge and relationship transfer. This study investigates the latter and identifies factors that influence the likelihood of its occurrence. Using a novel database that tracks the employment and client attachments of U.S. federal lobbyists, I show that repeated exchange with employees (firms) increases (decreases) the likelihood clients follow employees who switch firms. Structurally, multiplexity reduces the likelihood of client transfer and weakens the effect of employee–client repeated exchange, with the multiplexity effect strongest when team members have specialized expertise. By examining the main and interactive effects of repeated exchange, multiplexity, and specialized human capital, this study extends prior work by demonstrating how individual, organizational, and structural relationship characteristics affect client transfer and retention ex-post employee mobility. Managerial summary: When do clients follow employees who switch firms? What can firms do to guard against it? These questions are important in service-based industries where clients may become loyal to individual employees within the firm rather than to the firm itself. This study provides evidence that helps practicing managers: (a) identify which clients are most at risk of defecting if employees exit, and (b) structure relationships in ways that mitigate the likelihood that employee exit results in client loss. Findings suggest that a client is more likely to defect when she has extensive history working with the exiting employee, particularly if the employee was the sole link between the client and firm. Managers, however, can reduce the risk of client loss following employee exit by structuring relationships so that clients work with teams of employees rather than exclusively with an individual and by increasing the degree of specialization within these teams.]